A simulation method and laboratory brake friction dynamometer for tribology studies - Nivala, Peter Thompson, author; Radford, Donald W., advisor; Sakurai, Hiroshi, committee member; Heyliger, Paul Roy, 1958-, committee member (Colorado State University. Libraries, 2009)
Two of the most important parameters of brake system design are the frictional and wear capabilities of the rotor and pad materials. These parameters must meet minimum design requirements in an effort to enhance friction and reduce wear to improve the performance and life of brake system components. The frictional and wear performance of the rotor and pad materials can be assessed through laboratory brake dynamometer testing and evaluation. In the current study, a wear testing simulation and an inertia laboratory brake dynamometer were developed to resolve differences in wear rates of brake materials. Dynamometer testing was conducted to verify the logic of the simulation and the functionality of the dynamometer by measuring wear rates of brake rotor material samples, some of which were subjected to cryogenic heat treatment to modify their wear rates, at varying brake application pressures. Dynamometer testing established that the wear simulation and inertia laboratory brake dynamometer developed during the current study could function together as a suitable tribological experimental apparatus. Specifically, dynamometer testing demonstrated the ability of the experimental apparatus to resolve differences in wear rates of brake materials due to variations in brake application pressure at relatively short test durations; however, dynamometer test results did not show conclusive evidence to suggest an advantage in subjecting the rotor materials used in the current study to cryogenic treatment to lower the rotor or pad wear rates.
Department Head: Allan Thomson Kirkpatrick.